Carcass traits, nutrient composition and technological quality of monitor lizard (Varanus exanthematicus) meat produced in captivity in Benin - Tougan P. Ulbad; Biaou Honoré; Nago Gilles; Rebecca, Assa A.R; Dagbeto Bénedicte; Mensah A. Guy; Lognay Georges; Malaisse François; Théwis André (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Varanus exanthematicus (Bosc, 1792) is the most consumed reptile as bushmeat among wildlife species in Benin. The study aimed to characterize the functional properties and the nutritional values of its meat producer in captivity. Therefore, ten Varanus exanthematicus were slaughtered and their thigh and back muscles were used for the physic-chemical analyses. It comes out from the study that the total length, snout-vent length, the tail length, the wingspam length, the neck length, the tail circumference, the thorax depth and the thorax width were respectively 123 cm, 52 cm, 74cm, 34 cm, 11 cm, 16 cm, 4 cm and 8.5 cm. The live weight of the monitors, the weight of the hot carcass and the yield of the hot carcass are respectively 1920g, 1700g and 88.54%. The arms, the thigh and the tail represent respectively 15.58%, 20.58% and 25.88% of the hot carcass weight. Functionally, the pH value recorded at 24 hours post-mortem, the luminance, the red index, the yellow index and the water holding capacity were respectively 6.37; 44.18; 14.7; 16.18 and 28.1% for the thigh meat and were respectively 6.58, 45.61; 10.22; 16.18 and 26.4% for the back meat sampled without skin. Nutritionally, the dry matter, total ash, water, organic matter, fat and total nitrogen content of the meat are respectively 28%; 1.6%, 72%, 26.4%, 3.1% and 22.9%. It would be interesting to encourage the domestication trials of this species currently underway in Benin to not only promote food security through the use of unconventional resources, but also to reduce pressure on wildlife.